Use of rhu-GM-CSF in pulmonary tuberculosis patients: results of a randomized clinical trial - Pedral-Sampaio,Diana Brasil (2003)
It has been postulated that deficient or incomplete clinical and/or microbiological response to tuberculosis treatment is associated with cell-mediated immunological dysfunction involving monocytes and macrophages. A phase 2 safety trial was conducted by treating patients with either recombinant human granulocyte-macrophage colony-stimulating factor (rhu-GM-CSF) or a placebo, both in combination with anti-tuberculosis chemotherapy. Thirty-one patients with documented pulmonary tuberculosis were treated with rifampin/isoniazid for six months, plus pyrazinamide for the first two months. At the beginning of treatment, rhu-GM-CSF (125µg/M²) was randomly assigned to 16 patients and injected subcutaneously twice weekly for four weeks; the other 15 patients received a placebo. The patients were accompanied in the hospital for two weeks, then monthly on an out patient basis, for 12 months. Clinical outcomes were similar in both groups, with no difference in acid-fast bacilli (AFB) clearance in sputum at the end of the fourth week of treatment. Nevertheless, a trend to faster conversion to negative was observed in the rhu-GM-CSF group until the eighth week of treatment (p=0.07), after which all patients converted to AFB negative. Adverse events in the rhu-GM-CSF group were local skin inflammation and an increase in the leukocyte count after each injection, returning to normal 72 hours after rhu-GM-CSF injection. Three patients developed SGOP and SGPT > 2.5 times the normal values. All patients included in the GM-CSF group were culture negative at six months, except one who had primary TB resistance. None of the patients had to discontinue the treatment in either group. We conclude that rhu-GM-CSF adjuvant immunotherapy could be safely explored in a phase 3 trial with patients who have active tuberculosis.